Strategi Dakwah Membangun Ukhuwah Islamiyyah: Studi Kasus di Youth Islamic Study Club Al-Azhar Jakarta - Musofa, Kharis (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
This article aims to describe the da'wah strategy carried out at the Youth Islamic Study Club (YISC) Al-Azhar. The method used in this research is descriptive qualitative. The findings generated from this article are that the da'wah strategy carried out to build ukhuwah Islamiyah is carried out with three events: first, holding a recitation that prioritizes and discusses how important ukhuwah islamiyah is in the struggle for da'wah with the YIFEST (Youth Islamic Festival) event held at the state-owned mosque, Istiqlal. Second, holding MABIT (Malam Bina Iman dan Takwa) by inviting many Islamic communities in Jakarta and activities are held at night on holidays. Third, conducting Tabligh Akbar "MUSLIM UNITED" with the theme of the recitation that is often carried out is related to "ukhuwah Islamiyah".